THE ROLE OF ARTIFICIAL INTELLIGENCE IN EARLY DIAGNOSIS OF BREAST CANCER PATIENTS (KIUT Publication, 2025)
Breast cancer is one of the most common and deadly oncological diseases among women worldwide. Every year, millions of women are diagnosed with this disease, and many of them lose their lives due to late detection or delayed treatment. The prevention, early diagnosis, and effective treatment of breast cancer remain some of the most pressing issues of modern medicine.